Development of students’ concept images in analysis - Juter, Kristina (NOMAD Nordic Studies in Mathematics Education, 2009)
Students’ pre-knowledge and conceptual development in analysis were investigated at a teacher education program to reveal what pre-knowledge endured and how the students perceived the concepts a year after the course had ended. Questionnaires and interviews were used to collect data. Two students’ results are presented in more detail in the article. The study was cognitively framed with the influence of situated theories to take as many aspects of concept development into account as possible. The students showed numerous connections between concepts, but they were often unable to discern valid links from invalid links. The perceived richness from many connections causes unjustifiably strong self-confidence which prevents further work with the concept. A tool for classification of the students’ connections between concepts resulted from the analysis.